Connecting Theory, Research, and Practice in the Psychology of Creativity: An Introduction to a Special Issue. (28th November 2015) - Tan, Ai‐Girl
Abstract: A special issue "Connecting theory, research, and practice in the psychology of creativity" is compiled with contributions from creativity researchers across continents. The full papers were submitted by Beth Hennessey from the United States of America (U.S.), Maciek Karwowski from Poland, as well as Lene Tanggaard and Vlad Glaveanu from Denmark. The papers were blind‐reviewed. Three commentaries on these papers were authored by Anna Hui from Hong Kong China, James Kaufman from U.S., and Ai‐Girl Tan and Meng‐Ee Wong from Singapore. The special issue serves as a preliminary convergent effort to bridge theories and practices, to embrace multiple research methods of inquiry, and to explore a common ground for advancing knowledge of creativity in the science of psychology.